Establishment and characterization of in vivo orthotopic bioluminescent xenograft models from human osteosarcoma cell lines in Swiss nude and NSG mice. (23rd February 2018) - Marques da Costa, Maria Eugenia; Daudigeos‐Dubus, Estelle; Gomez‐Brouchet, Anne; Bawa, Olivia; Rouffiac, Valerie; Serra, Massimo; Scotlandi, Katia; Santos, Conceição; Geoerger, Birgit; Gaspar, Nathalie
Abstract: Osteosarcoma is one of the most common primary bone tumors in childhood and adolescence. Metastases occurrence at diagnosis or during disease evolution is the main therapeutic challenge. New drug evaluation to improve patient survival requires the development of various preclinical models mimicking at best the complexity of the disease and its metastatic potential. We describe here the development and characteristics of two orthotopic bioluminescent (Luc/mKate2) cell‐derived xenograft (CDX) models, Saos‐2‐B‐Luc/mKate2‐CDX and HOS‐Luc/mKate2‐CDX, in different immune (nude and NSG mouse strains) and bone (intratibial and paratibial with periosteum activation) contexts. IVIS SpectrumCT system allowed both longitudinal computed tomography (CT) and bioluminescence real‐time follow‐up of primary tumor growth and metastatic spread, which was confirmed by histology. The murine immune context influenced tumor engraftment, primary tumor growth, and metastatic spread to lungs, bone, and spleen (an unusual localization in humans). Engraftment in NSG mice was found superior to that found in nude mice and intratibial bone environment more favorable to engraftment compared to paratibial injection. The genetic background of the two CDX models also led to distinct primary tumor behavior observed on CT scan. Saos‐2‐B‐Luc/mKate2‐CDX showed osteocondensed, HOS‐Luc/mKate2‐CDX osteolytic morphology. Bioluminescence defined a faster growth of the primary tumor and metastases in Saos‐2‐B‐Luc/mKate2‐CDX than in HOS‐Luc/mKate2‐CDX. The early detection of primary tumor growth and metastatic spread by bioluminescence allows an improved exploration of osteosarcoma disease at tumor progression, and metastatic spread, as well as the evaluations of anticancer treatments. Our orthotopic models with metastatic spread bring complementary information to other types of existing osteosarcoma models. Abstract : New osteosarcoma preclinical models in an orthotropic bone setting with the possibility to follow in vivo both primary tumor growth and metastatic spread will further help testing and development of new drug in this disease which outcome has not improved since several decades.